Osteoclast-like cells form in long-term human bone marrow but not in peripheral blood cultures. - Takahashi, N (1989)
Transplantation studies have suggested that peripheral blood mononuclear cells contain precursors for osteoclasts. Thus we tested the capacity of peripheral blood monocytes to form osteoclasts in long-term culture. We have reported previously that mononuclear cells from feline, baboon, and human marrow form osteoclast-like cells in long term cultures. Further, the formation of these cells is increased in response to bone resorption stimulatory agents such as PTH, interleukin 1, and transforming growth factor alpha. We now report that these cells show characteristic cytoplasmic contraction with calcitonin and form resorption lacunae when cultured on sperm whale dentine. Thus, these bone marrow-derived multinucleated cells fulfill the functional criteria for osteoclasts. Although cultured peripheral blood monocytes can be induced to form multinucleated cells with 1,25-dihydroxyvitamin D3, these cells did not show similar responses to the osteotropic factors as multinucleated cells formed in the bone marrow cultures multinucleated cells. These results indicate that osteoclasts or cells closely related to osteoclasts form in long-term human bone marrow cultures. In contrast, few mononuclear cells in the peripheral blood appear capable of forming osteoclasts under the culture conditions used in these experiments.